Subclinical vestibular dysfunction in type 1 diabetes mellitus. (15th March 2021) - Moossavi, Abdollah; Shaabani, Moslem; Nasli Esfahani, Ensieh; Vahedi, Mohsen; Enayati, Zakaria
Abstract: Objective: Metabolic changes that occur in diabetes mellitus (DM) can interfere with the energy supply for the metabolic active inner ear, resulting in vestibular impairments. The purpose of this study was to evaluate the effects of type 1 DM on the vestibular system using a vestibular test battery. Methods: Vestibular function of fifteen asymptomatic type 1 DM patients with a mean age of 28 years (SD= 5.80) and 16 healthy controls with a mean age of 26 years (SD = 2.86), respectively, was assessed using video-head impulse test (vHIT), ocular and cervical vestibular evoked myogenic potential (o/cVEMP), and subjective visual vertical and horizontal (SVV/SVH). Results: vHIT response was pathological, in approximately 6.66% of canals. The peak-to-peak p1-n1 amplitude in cVEMP and p1 latency of oVEMP were significantly smaller in the left ear ( p = .018) and lengthened in both ears ( p = .004) of DM participants compared to the healthy group, respectively. The mean deviation of dynamic SVV (Opto +40/s) was significantly increased ( p = .022). Conclusion: Asymptomatic DM can influence the vestibular system, especially the otolith organs, indicating the presence of subclinical vestibular dysfunction (VD) prior to the onset of vestibular manifestations, which can be detected using appropriate vestibular tests. Furthermore, DM might have selective or chronological order effects on the human vestibular system, with the otolith system damage preceded the semicircular canals. Thus, early and periodic vestibular assessment of DM patients for detecting possible latent VD and preventing further problems is advisable. However, further clinical studies are required.